Crime, unemployment and labor market programs in turbulent times - Anna Nilsson; Jonas Agell (Institute for Labour Market Policy Evaluation (IFAU), 2003)
We exploit the exceptional variation in municipality-level unemployment and spending on labor market programs in Sweden during the 1990s to identify the impact of unemployment and programs on crime. We identify a statistically significant effect of unemployment on the incidence of overall crime, burglary, auto-theft and drug possession. A calculation suggests that the sharp reduction in unemployment during the later 1990s may have reduced burglary and auto-theft with 15 and 20 percent, respectively. After addressing several specification issues, we conclude that there is at best weak evidence that labor market programs general ones and those specifically targeted to the young help to reduce crime.
Keywords: J00; K40; 330; Crime; unemployment; labor market programs; panel data